Fabrication of Hybrid Materials Based on Waste Polyethylene/Porous Activated Metakaolinite Nanocomposite as an Efficient Membrane for Heavy Metal Desalination Processes - Mahmoud F. Mubarak; Mohamed A. Zayed; Ayman Nafady; Abeer E. L. Shahawy (Adsorption Science & Technology)
Hybrid nanostructure materials derived from activated metakaolinite are of growing importance due to their intriguing structural/functional properties and promising biomedical/environmental applications, especially designing desalination membranes. Herein, we report procedures to design and fabricate membranes based on waste polyethylene/porous activated-metakaolinite thin film nanocomposites (WPE/PAMK-TFN). It has been devoted to improving water desalination processes, where efficient removal of trace level (~250 ppm) of toxic heavy metals such as Cd(II), Pb(II), and Cu(II) ions from synthetic wastewater solutions was highly accomplished. Physicochemical techniques such as X-ray diffraction (XRD), surface analysis (BET), and Fourier transform infrared spectroscopy (FTIR) have been extensively employed to elucidate the structure/composition of the prepared nanomaterials. The effect of concentration (0–0.5 wt%) of porous activated-metakaolinite (PAMK) on water permeation was investigated. The results obtained revealed that 0.5 wt% of PAMK clay particles produced the highest dispersion, as evident by SEM images of the nanocomposite membranes. Significantly, the constructed membrane showed marked improvements in porosity, hydrophilicity, and hydraulic resistance. Moreover, elemental mapping studies have confirmed the intercalation of activated bentonite clay within the polymer matrix. The obtained results demonstrated that increased flux and rejection capability of membranes occurred at high clay dosage. In contrast, the low rejection capability was observed at either lower pH and higher initial feed concentrations. Ultimately, for 250 ppm of Cd(II), Pb(II), and Cu(II) ions, the constructed membranes showed maximum removal capability of 69.3%, 76.2%, and 82.5% of toxic cations, respectively.